هزراندن و بنەماکانی زەینی و فەلسەفیەکان لە نێو "هونەری پاش میتافیزیک"دا. ڕووگەی هونەرییە هاوچەرخەکان بە نموونە - خضر, كارزان احمد (Sulaimani Journal for Humanities, 2021)
The central aim of intellectual research is to describe, explain and expound a theme which has not formerly been explored in the realm of Art history, thought and philosophy. Intellectual research has several objectives which all serve to illuminate the path of that field. The same principle also applies to the field of art. Therefore, probing a complex area such as the philosophy of art is not a straightforward task and it certainly requires a painstaking effort, insightful knowledge and a distinctive practical experience. The need for these underlying skills is particularly apparent in this region because contemporary art has not yet formulated itself properly. What is art? Why art has hitherto been a pivotal focus of philosophers? What is the boundary between art and non-art? What are the inquiries of contemporary art? And so on. To understand the existential questions in this research paper, we need to demonstrate the worldview of art and the history of aesthetics. Thus, this research paper aims to investigate the intellectual (mind) bases of modern art on one hand, and prominent facets of art on the other hand.